Photosystem II Excitation Pressure and Development of Resistance to Photoinhibition (II. Adjustment of Photosynthetic Capacity in Winter Wheat and Winter Rye). - Gray, G. R. (1996)
Winter wheat (Triticum aestivum L. cv Monopol), spring wheat (Triticum aestivum L. cv Katepwa), and winter rye (Secale cereale L. cv Musketeer) grown at 5[deg]C and moderate irradiance (250 [mu]mol m-2 s-1) (5/250) exhibit an increased tolerance to photoinhibition at low temperature in comparison to plants grown at 20[deg]C and 250 [mu]mol m-2 s-1 (20/250). However, 5/250 plants exhibited a higher photosystem II (PSII) excitation pressure (0.32-0.63) than 20/250 plants (0.18-0.21), measured as 1 - qP, the coefficient of photochemical quenching. Plants grown at 20[deg]C and a high irradiance (800 [mu]mol m-2 s-1) (20/800) also exhibited a high PSII excitation pressure (0.32-0.48). Similarly, plants grown at 20/800 exhibited a comparable tolerance to photoinhibition relative to plants grown at 5/250. In contrast to a recent report for Chlorella vulgaris (D.P. Maxwell, S. Falk, N.P.A. Huner [1995] Plant Physiol 107: 687-694), this tolerance to photoinhibition occurs in winter rye with minimal adjustment to polypeptides of the PSII light-harvesting complex, chlorophyll a/b ratios, or xanthophyll cycle carotenoids. However, Monopol winter wheat exhibited a 2.5-fold stimulation of sucrosephosphate synthase activity upon growth at 5/250, in comparison to Katepwa spring wheat. We demonstrate that low-temperature-induced tolerance to photoinhibition is not a low-temperature-growth effect per se but, instead, reflects increased photosynthetic capacity in response to elevated PSII excitation pressure, which may be modulated by either temperature or irradiance.